2021
DOI: 10.1159/000516907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orthokeratology on Axial Length Elongation in Anisometropes

Abstract: <b><i>Introduction:</i></b> This study aimed to investigate the therapeutic effects of overnight orthokeratology (OK) lenses on anisometropes. <b><i>Methods:</i></b> We enrolled 178 anisometropes from August 2015 to August 2017. We then divided these patients into 2 parts depending on them wearing either monocular or binocular OK lenses. In part one, 47 monocular myopic subjects (25 males and 22 females) were treated with OK lenses in the myopic eyes only. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…In this experiment, uncorrected visual acuity and refraction were higher, while axial length was reduced 1 to 6 months after overnight orthokeratology lens wear treatment than in children treated with spectacles. When overnight orthokeratology lens wear is used to correct visual acuity, the main reason for its success depends on the equivalent refraction, while the change of equivalent refraction is determined by the change of curvature [20]. In this experiment, the uncorrected visual acuity and refraction of children 1 ~ 6 months after overnight orthokeratology lens wear treatment showed a gradually improving trend, which was in line with the characteristics of continuous uctuation of keratometry.Therefore, overnight orthokeratology lens wear can improve uncorrected visual acuity and refraction, and reduce axial length in the treatment of myopic children, which is conducive to the recovery of children.…”
Section: Resultssupporting
confidence: 62%
“…In this experiment, uncorrected visual acuity and refraction were higher, while axial length was reduced 1 to 6 months after overnight orthokeratology lens wear treatment than in children treated with spectacles. When overnight orthokeratology lens wear is used to correct visual acuity, the main reason for its success depends on the equivalent refraction, while the change of equivalent refraction is determined by the change of curvature [20]. In this experiment, the uncorrected visual acuity and refraction of children 1 ~ 6 months after overnight orthokeratology lens wear treatment showed a gradually improving trend, which was in line with the characteristics of continuous uctuation of keratometry.Therefore, overnight orthokeratology lens wear can improve uncorrected visual acuity and refraction, and reduce axial length in the treatment of myopic children, which is conducive to the recovery of children.…”
Section: Resultssupporting
confidence: 62%
“…In a 2-year retrospective study, orthokeratology lenses reduced myopia progression by 0.85 D and axial length by 0.19 mm in Japanese children 30 . In another 2-year retrospective study, orthokeratology lenses reduced axial length progression by 0.50 mm in Chinese children 31 . The axial length growth was significantly reduced in bilateral myopic anisometropia with greater effects in the more myopic eye (difference of 0.07 mm).…”
Section: Resultsmentioning
confidence: 94%
“…30 In another 2-year retrospective study, orthokeratology lenses reduced axial length progression by 0.50 mm in Chinese children. 31 The axial length growth was significantly reduced in bilateral myopic anisometropia with greater effects in the more myopic eye (difference of 0.07 mm).…”
Section: Orthokeratologymentioning
confidence: 93%
See 1 more Smart Citation
“…However, the effectiveness of OK varies greatly among different studies, 3 and its mechanism for myopia control remains unclear. 4 Recent studies indicated that increments of choroidal thickness occurred after OK application. 5,6 Then it is speculated that the underlying mechanism of myopia control using OK could be associated with the change in choroidal thickness.…”
mentioning
confidence: 99%